Human Resources in Medical Organizations in the Republic of Kazakhstan - Baiganova, Zhuldyz (Asian Journal of Pharmaceutics (AJP), 2018)
Background: During two decades, Kazakhstan has been conducting various reforms, and specifically in the healthcare sector, which inherited the Soviet Union system. Timely implementation of governmental programs depends on the human resources (HR) potential opportunities. One of the main dimensions of healthcare system development is planning and establishing HR, based on the healthcare needs and requirements. National observatory of HR in health care was established for the realization of healthcare system development. The research that we had been conducted is dedicated for providing evaluation and assessment of the present HR performance and activity in healthcare organizations of the Republic of Kazakhstan. Aim: The aim of this research is to present critical evaluation and assessment of the present HR activities in healthcare organizations of the Republic of Kazakhstan. Result and Discussion: On analysis of research data, it was found out that there is an extreme need in elaboration and development of the HR institution capacity in Republic of Kazakhstan. Second, power base and establishment of the national observatory of HR in health care in Republican center for development can be mentioned as an upward trend. Conclusion: There is a demand in conducting professional training among HR managers in the perspective of providing talent pipeline for medical organizations and implementation of professional development programs HR in medical organizations.